Variasi Metodologi Ilmu Tarannum: Suatu Perbincangan Kritis: Methodological Variations in Tarannum Science: A Critical Discussion - Muhammad Lukman b. Ibrahim; Anuar b. Hasin; Zainora b. Daud; Mohd Azhar Abdullah (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Al-Quran is the highest miracle of the Prophet Muhammad saw, which includes various disciplines of knowledge including the knowledge of Qiraat, tafsir and tarannum. In accordance with its meaning, this discipline of tarannum emphasizes the processing of sound and beautifying the sound according to the process of certain tones, beats and rhythms. Although it is generally understood that knowledge in this discipline is applied to appreciate the uslub of al-Quran, but wihin the public society, they are not clear about the differences in the variation of knowledge methodology in this field. Therefore, this article aims to analyze some methodologies of tarannum science that should be followed by every reciter of the Qur'an. This study applies qualitative research methods with inductive and deductive methodologies, to identify the best methodological variations available in the science of tarannum. The results of the study found that there is a great importance in the implementation and use of the right methodology in the science of tarannum, this is because without it, it will inhibit the method of proper reading presentation. Even these methods must be diversified without running away from the methods that are imposed on the limits of recitation advocated by the Qurra.